2015
DOI: 10.5505/turkhijyen.2015.14880
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility of microbiota members Escherichia coli strains isolated from stool samples of patients attended Kırıkkale Yüksek İhtisas Hospital in ten months

Abstract: Objective: Antibiotic resistance has turned into a global public health problem in all over the world. Intestinal flora bacteria perform many important functions for human health. As a member of microbiota Escherichia coli cause many infections. This study was aimed to determine antibiotic susceptibility of microbiota member E. coli isolates against to the antibiotics that used in treatment. Methods:One hundred and fifty stool samples, which were sent to Kırıkkale Yüksek İhtisas Hospital microbiology laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Similar to other investigations, different antibiotic resistance patterns were observed in UPEC compared with commensal isolates [ 31 , 32 ]. We found that the resistance rate of commensal isolates to third-generation cephalosporins and amikacin was higher than was observed in reports from other countries [ 31 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other investigations, different antibiotic resistance patterns were observed in UPEC compared with commensal isolates [ 31 , 32 ]. We found that the resistance rate of commensal isolates to third-generation cephalosporins and amikacin was higher than was observed in reports from other countries [ 31 33 ].…”
Section: Discussionsupporting
confidence: 88%